Invasive Candida infections in surgical patients in intensive care units: a prospective, multicentre survey initiated by the European Confederation of Medical Mycology (ECMM) (2006–2008). (January 2015) - Klingspor, L.; Tortorano, A.M.; Peman, J.; Willinger, B.; Hamal, P.; Sendid, B.; Velegraki, A.; Kibbler, C.; Meis, J.F.; Sabino, R.; Ruhnke, M.; Arikan-Akdagli, S.; et al.
Abstract: A prospective, observational, multicentre study of invasive candidosis (IC) in surgical patients in intensive care units (ICUs) was conducted from 2006 to 2008 in 72 ICUs in 14 European countries. A total of 779 patients (62.5% males, median age 63 years) with IC were included. The median rate of candidaemia was 9 per 1000 admissions. In 10.8% the infection was already present at the time of admission to ICU. Candida albicans accounted for 54% of the isolates, followed by Candida parapsilosis 18.5%, Candida glabrata 13.8%, Candida tropicalis 6%, Candida krusei 2.5%, and other species 5.3%. Infections due to C. krusei (57.9%) and C. glabrata (43.6%) had the highest crude mortality rate. The most common preceding surgery was abdominal (51.5%), followed by thoracic (20%) and neurosurgery (8.2%). Candida glabrata was more often isolated after abdominal surgery in patients ≥60 years, and C. parapsilosis was more often isolated in neurosurgery and multiple trauma patients as well as children ≤1 year of age. The most common first-line treatment was fluconazole (60%), followed by caspofungin (18.7%), liposomal amphotericin B (13%), voriconazole (4.8%) and other drugs (3.5%). Mortality in surgical patients with IC in ICU was 38.8%. Multivariate analysis showed that factors independently associated with mortality were: patient age ≥60 years (hazard ratio (HR) 1.9, p 0.001), central venous catheter (HR 1.8, p 0.05), corticosteroids (HR 1.5, p 0.03), not receiving systemic antifungal treatment for IC (HR 2.8, p <0.0001), and not removing intravascular lines (HR 1.6, p 0.02).